Expression and significance of TGF-β1 in Infant Asthma Model: TGF-β1 in Infant Asthma Model - Yuan, Jiabo; Zhang, Wei (Cellular and Molecular Biology, 2022)
This article aimed to study the expression and role of TGF-β1 in young rat asthma. The experimental method in this paper is to replicate the asthma model by aerosolization of egg protein. The young rats with asthma were sacrificed after 2, 4 and 8 weeks. Reverse transcription polymerase chain reaction (RT-PCR) was used to detect the mRNA of TGF-β1 and α-SMA. The expression level was detected by the immunohistochemical staining method to detect the protein expression of TGF-β1, α-SMA, Smad3, Smad4 and Smad7 in bronchopulmonary tissues. At the same time, the image analysis method was used to measure the airway morphological parameters of young rats. The experimental results showed that the expression of TGF-β1 in the lung tissue of young rats in the asthma group was increased after two weeks of the challenge. Compared with the control group, the difference was significant (P<0.05); the expression of TGF-β1, α-SMA and mRNA in the 4-week group was significantly higher, compared with the control group and the 2-week challenge group, the difference was significant (P<0.05). Therefore, the change of asthma airway remodeling is a dynamic process. The TGF-β1 pathway presents a dynamic process in the airway remodeling model of young asthmatic rats. Among them, TGF-β1 induces the division and proliferation of airway fibroblasts and promotes fibroblasts. The cells transform into myofibroblasts and increase the synthesis of fibronectin and collagen, suggesting that it plays an important role in asthma inflammation and pulmonary fibrosis.